Optimizing Science Process Skills Through the Use of Simple Steam Power Plant Models in Middle School Physics Education - Johari, Johari (Tekno - Pedagogi : Jurnal Teknologi Pendidikan, 2024)
This study aims to evaluate the effectiveness of using a simple steam power plant prop in improving the science process skills of eighth grade students at Pesantren Guppi Samata Junior High School. The importance of this study lies in the need for innovative teaching methods that can improve students' engagement and understanding in science education, especially considering the limitations of traditional laboratory resources. A quasi-experimental design with a pretest-posttest control group was used, involving purposive sampling of two groups: an experimental group that used a simple steam power plant prop and a control group that did not use the prop. Data were collected through a structured multiple-choice test that assessed various aspects of science process skills and were analyzed using descriptive statistics, normality tests, and independent t-tests. The findings showed that the experimental group significantly outperformed the control group in the posttest (p = 0.000), indicating that the simple steam power plant prop effectively facilitates better understanding of scientific concepts through hands-on learning. The novelty of this study lies in its focus on the use of simple and accessible teaching props to improve practical skills in science education. The results of this study suggest that incorporating these tools into teaching can improve educational outcomes, and offer a valuable resource for educators facing limited laboratory facilities.